Crashworthiness design of a sponge-inspired multicell tube under axial crushing. (15th April 2023) - Li, Yansong; Hu, Dayong; Yang, Zhenyu
Highlights: Bionic design inspired by the microstructure of deep-sea glass sponge was introduced to enhance the axial energy absorption for the thin-walled tube. SEA was improved by 32.2% to 53.1% and 7.7% to 28.1% when compared to conventional multi-cell tubes and other bio-inspired tubes, respectively. The performance of energy absorption could be significantly improved by the introduction of hierarchical designs. A theoretical model was developed based Simplified Super Folding Element (SSFE) theory to predict the mean crushing force of UCGS. Abstract: A novel bio-inspired multicell tube (named UCGS), mimicking the unique double-diagonally reinforced configuration in the unit cell of glass sponge (GS), was proposed and fabricated by additive manufacturing. Crashworthiness analysis of UCGS was carried out via ABAQUS/Explicit and validated by quasi-static axial crushing tests. Due to its distinctive double-diagonal reinforcing strategy, the results demonstrated that UCGS had a high specific energy absorption ( SEA ) of up to 30.7 J/g, which was 32.2% to 53.1% higher than that of conventional multi-cell tubes and 7.7% to 28.1% higher than that of other bio-inspired tubes, respectively. Subsequently, the effects of geometric parameters and hierarchical designs on the energy absorption performance were investigated by numerical simulation. By choosing the proper geometric parameters and hierarchical design, the energy absorption capability of the presented bio-inspired multicell tube could be further increased, and the SEA was 3.3%–39% greater than the original design. Finally, a theoretical model was proposed to predict the mean crushing force, which was in good agreement with the numerical results. This study shed light on a deep understanding of the deformation mechanisms of bio-inspired tubes, and provided inspirations for designing and optimizing of energy absorber with high performance. Graphical abstract: Image, graphical abstract